Trends in the Processes of Lipid Peroxidation and Antioxidant Defense in Puerperas with Eclampic Coma - I. Kh. Khapiy; Yu. S. Podolsky (Общая реаниматология)
Objective: to study the impact of the processes of lipid peroxidation (LPO) and antioxidant defense (AOD) on consciousness recovery trends in puerperas with eclampic coma. Subjects and methods. Two patient groups were examined. Group 1 (control) comprised 12 puerperas delivered by elective cesarean section; Group 2 included 26 puerperas with eclampic coma, delivered by emergency cesarean section. To evaluate the efficacy of cytoflavin in leveling oxidative stress, Group 2 was divided into 2 subgroups: 2a) non-cytoflavin and 2b) cytoflavin. Investigations were made in the puerperas with eclampic coma at four stages: 1) on admission (on days 1—2 after the first convulsive attack); 2) on days 2—3 after admission); 3) during emergence from coma state; 4) before transition from an intensive care unit. Results. Comparison of the results obtained in two groups suggests that the eclampic coma puerperas showing a significant increase in lipid peroxides in the presence of AOD exhaustion have uncompensated oxidative stress. Comparative assessment of subgroups 2a and 2b established that incorporation of cytoflavin into the complex therapy of puerperas reduced the duration of coma. Conclusion. The use of cytoflavin results in a rapider normalization of LPO and an enhancement of AOD in puerperas with coma, which contributes to an earlier emergence from coma. Key words: eclampic coma, lipid peroxidation, antioxidant defense, consciousness recovery, cytoflavin.